Securing Text Messages Using E2EE (End-To-End Encryption) on Instant Messaging Applications - Wasis Pancoro (Universitas Kristen Satya Wacana, 2024)
With the development of technology in communication, many applications make it easy to send messages. security in sending messages is something that cannot be excluded. E2EE (End-to-end encryption) is one of the most encryption for securing messages. in the discussion of literature review produces information on how applications such as whatsApp, Skype, Facebook messenger, line and viber implement E2EE in encrypting text messages specifically.